(untitled) (KIUT Publication, 2025)
The COVID-19 pandemic, which began in 2020, had a profound impact on the global education system. As a result of quarantine measures adopted to protect public health, traditional learning processes were temporarily suspended, and forms of distance education were introduced. This transition, however, was particularly challenging in the field of medical education.